THE EFFECT OF WARM WATER SOAK HYDROTHERAPY AND PASSIVE ROM EXERCISES ON THE MUSCLE STRENGTH OF STROKE PATIENTS - Hasbi Dzikri ZF, Moh; Cahyati, Yanti; Adini, syaukia (Journal of Nursing Culture and Technology, 2025)
Background: Stroke is characterized by the death of brain tissue, which occurs due to reduced blood and oxygen flow to the brain due to blockage of blood vessels, which causes motor disorders and decreased muscle strength. So, efforts are needed to increase muscle strength with Warm Water Soak Hydrotherapy and Passive ROM Exercises. Objective: This study aims to determine the effect of warm water immersion hydrotherapy and ROM exercises on muscle strength in stroke patients. Method: This research used a pre-experiment, one-group pretest post-test design. Sampling used a purposive sampling technique with a sample size of 20 people. The statistical test used is the paired t-test with a significance of 0.05. Results: There was a difference in the average muscle strength values before and after being given warm water immersion hydrotherapy and passive ROM exercises with a p-value of 0.001. Conclusions: There is an effect of warm water immersion hydrotherapy and passive ROM exercises on muscle strength.